A Multinational Study to Compare Prevalence of Atopic Dermatitis in the First Year of Life - Mallol-Villablanca, E (Blackwell Publishing Ltd, 2015)
Background: Atopic dermatitis (AD) is common in childhood, with peak prevalence in early childhood. However, international comparisons of prevalence have focused on older children. We analysed differences in prevalence rates of AD and the associations with putative risk and protective factors, among infants in two European and two Central American countries. Methods: In 1-yr old infants participating in the International Study of Wheezing in Infants (EISL), prevalence of AD and putative risk and protective factors were assessed by a questionnaire applied to parents. For each risk/protective factor summary, odds ratios with 95% confidence intervals were calculated by means of random effects meta-analysis. Results: Data from 9803 infants were analysed. AD prevalence varied from 10.6% (Valencia, Spain) to 28.2% (San Pedro Sula, Honduras). Average AD prevalences were lower in Europe (14.2%) than in Central America (18.2%, p < 0.01). Consistent with older children, presence of siblings decreased (OR 0.82 [0.72-0.94]), whereas family history of asthma (OR 1.32 [1.10-1.59]), rhinitis (OR 1.33 [1.14-1.54]) and atopic dermatitis (OR 2.40 [1.89-3.05]) increased the risk of infantile AD. However, gender, family size, breastfeeding and socio-economic status were not associated with AD prevalence. Conclusions: This study shows almost threefold differences in the prevalence of AD in infancy between countries. Risk and protective factors involved in the expression of infantile AD differ from those in older children, possibly suggesting a different pathophysiology. There is a need for additional international epidemiological surveys on AD in young children, the peak prevalence age of this condition. © 2015 John Wiley & Sons A/S. Published by John Wiley & Sons Ltd.